FACTORS AFFECTING USER'S ACCEPTANCE OF ADOPTING BIOMETRICS TECHNOLOGIES USING THE TAM MODEL - Zihan Kalila Gusnan; Rio Guntur Utomo (Informatika, Universitas Jenderal Soedirman, 2024)
User privacy and security concerns hinder the adoption of biometric authentication technology in Indonesia, especially when consumers are still determining how their biometric data will be stored, accessed and used. This research aims to investigate the variables that influence the adoption of biometric authentication technology in Indonesian society. The Technology Adoption Model is used in this research to estimate the impact of different parameters and investigate the importance of novel elements in adopting biometric authentication. Several factors are examined to see how they affect Actual System Use (ASU), including Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Trust & Security (TS), Perceived Privacy (PP), Attitude towards Using Technology (ATU), and Behavioral Intention to Use (BIU). New theories are presented in this study, focusing on the relationship between PP and BIU, which is supported by respondent data. The results show the rejection of two hypotheses: first, the effect of PU on BIU may not be strong enough to influence user intention, and other variables may be at play; second, the effect of PEOU on BIU implies that perceived ease of use alone may not be sufficient to influence user intention. BIU has a major impact on the adoption of biometric authentication technologies. Furthermore, this research found that compared to PU and PEOU, the original components of TAM BIU are more influenced by variables such as ATU, PP and TS. These results suggest that new considerations such as privacy, trust, and security are more influential in shaping usage intention in biometric authentication.